(untitled) (International Journal of Innovative Computing, 2021)
Infographics is a visual representation of data. Today, people learn faster and remember things more efficiently and effectively through the use of text and visuals than using the conventional textual method alone. Infographics can be used in visualization to enhance data interpretation and knowledge discovery. Many businesses use infographic elements that are hard to digest and understand. Visualization can be insufficient or ineffective, thus messages can be transferred well or they can be wrongly transferred. Businesses with lack of graphical representation skills usually meet with this kind of challenge. Preliminary study has found that transportation companies may not follow any design principle to design infographics. This can cause data to be poorly defined with uninteresting graphics which eventually do not trigger target audiences’ interest or unable to engage them. Besides, this process can affect the businesses’ revenues and customers’ satisfaction. A qualitative method was applied in this study. A design principle for public transportation infographic was developed based on three main principles which were Gestalt theory, components of infographics and components of public transportation. Gestalt theory introduces the theory of similarity, figure-ground, proximity, common region, focal point, closure, and continuity. Components of infographic include visual element, content element, and knowledge. Components of public transportation are unit of carriage, transportation terminals, travel directions and durations, safety, accessibility, reliability, and fares. A qualitative methodology was applied to evaluate the proposed principles. Five experts in infographics and visualization were assigned to evaluate the reliability of both the questionnaire and the infographic design principles. Findings from the expert’s review show the content validity index 0.95 for questionnaire and 0.89 for the design principle Infographic. Therefore, the result is acceptable. It is hoped that the developed design principle in public transportation will give good impacts in developing and enhancing infographics.